The effectiveness of acceptance and commitment therapy on fear of negative evaluation and anxiety in women facing divorce - Ahmadi Tabar , Fatemeh; Hasanpour, Esmat (Social Determinants of Health, 2024)
Background: The study's goal was to find out how well acceptance and commitment-based treatment worked for women going through divorce who were afraid of being negatively evaluated and experiencing anxiety. Methods: Women considering divorce who sought help from family counseling facilities in Kerman City during the first three months of 2013 were the subjects of this semi-experimental pre-test-post-test study, which included a control group. The samples were split into two groups of 15 individuals at random. In an experiment, eight 60-minute mindfulness training sessions were given to one group. For the control group, no particular treatment approach was offered. A post-test was administered to both groups following the conclusion of the treatment period. The Fear of Negative Evaluation Questionnaire (BFNES) and Wells Anxiety were among the instruments utilized. For analysis, multivariate analysis of variance and covariance were employed. Results: According to the findings, women going through a divorce who received treatment based on acceptance and commitment experienced less anxiety and fear of negative evaluation; the linear combination of anxiety and fear of negative evaluation was affected by this treatment by 0.903. Anxiety was reduced by 0.807%, and fear of a negative evaluation was reduced by 0.685% with acceptance and commitment-based therapy. Conclusion: Psychologists should use the acceptance and commitment-based therapy approach along with other treatment approaches to help women going through divorce feel less anxious and afraid of being negatively evaluated. Research indicates that this approach may be extremely effective.